2018
DOI: 10.1002/asia.201800996
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Metabolic Labeling of Glycoconjugates in Polarized Primary Cerebral Cortical Neurons

Abstract: The spatial distribution of cell-surface glycoconjugates in the brain changes continuously, reflecting neurophysiology especially in the developing phase, but their functions and fates mostly remain unexplored. Their spatiotemporal distribution is particularly important in polarized neuronal cells, such as cerebral cortical neurons composed of a soma and neurites. In this work, we dually labeled sialic acid (Sia5Ac) and N-acetylgalactosamine/glucosamine (GalNAc/GlcNAc) by a neurocompatible strategy of metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…For example, glial cells, such as astrocytes, play supporting roles in the brain. Relevant reports showed that the in vitro neurotoxicity of unnatural monosaccharides to primary hippocampal neurons was mitigated when a hippocampal tissue was used 26,28 or a neuron/astrocyte coculture was employed. 27 In this respect, it could be explained that the coculture system of neuron and glia (2:1) did not show the neurotoxicity of CBD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, glial cells, such as astrocytes, play supporting roles in the brain. Relevant reports showed that the in vitro neurotoxicity of unnatural monosaccharides to primary hippocampal neurons was mitigated when a hippocampal tissue was used 26,28 or a neuron/astrocyte coculture was employed. 27 In this respect, it could be explained that the coculture system of neuron and glia (2:1) did not show the neurotoxicity of CBD.…”
Section: Resultsmentioning
confidence: 99%
“…19 H 2 O 2 has been used as a model molecule to study oxidative stress-induced neural death and also to screen neuroprotective agents on the cultured neurons. 16,[20][21][22][23][24][25] As our on-going research program on neurochemistry and neurophysiology, [26][27][28][29][30][31] this study investigates the neuroprotective effect of CBD against H 2 O 2 in the hippocampal neuron culture.…”
Section: Introductionmentioning
confidence: 99%
“…In short, the sandwich coculture of neurons and astrocytes was carried out by placing the astrocytecultured plate parallel to the neuron-cultured plate with a narrow space in a face-to-face mode. [31,32] The sandwich platform makes it possible to analyze only neuron-cultured plate with the minimization of astrocyte contamination in the analysis. It also has been known that the supportive effects of astrocytes in the platform lead to the healthy growth of neurons: for example, most neurons die within 5 days in the neuron-alone culture, while neurons in the sandwich coculture with astrocytes survive healthily for more than 2 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28] Our group also has reported that the neuron-astrocyte coculture in a sandwich platform abolishes the neurotoxicity of unnatural monosaccharides in metabolic labeling of the sialoglycans localized in neurons. [29][30][31] Therefore, it is equally crucial to investigate the neuronal responses to CBD under the support of astrocytes, for better understanding of the CBD actions to neurons in a more in-vivo-relevant manner. In this work, we studied the neuronal responses to CBD in the neuron-astrocyte coculture system, showing that astrocytes have the capability for rescuing neurons against CBD-induced damages, such as increase of intracellular calcium concentration ([Ca 2+ ] i ) and mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, studies from the Choi group demonstrated that per- O -acetylated N -azidoacetylhexsosamine (Ac 4 HexNAz) including Ac 4 ManNAz and Ac 4 GalNAz were cytotoxic to cultured primary neurons. Ac 4 ManNAz at concentrations above 50 μM suppressed neurite development and caused cell death in primary rat hippocampal neurons in a dose-dependent manner . Similar adverse effects were observed in rat cortical neurons with Ac 4 ManNAz as well as Ac 4 GalNAz . The mechanism of per- O -acetylated sugar-induced cytotoxicity in primary neurons remains unclear.…”
Section: Introductionmentioning
confidence: 99%